2016
DOI: 10.1111/febs.13749
|View full text |Cite
|
Sign up to set email alerts
|

A cis‐prenyltransferase from Methanosarcina acetivorans catalyzes both head‐to‐tail and nonhead‐to‐tail prenyl condensation

Abstract: Cis‐prenyltransferase usually consecutively catalyzes the head‐to‐tail condensation reactions of isopentenyl diphosphate to allylic prenyl diphosphate in the production of (E,Z‐mixed) polyprenyl diphosphate, which is the precursor of glycosyl carrier lipids. Some recently discovered homologs of the enzyme, however, catalyze the nonhead‐to‐tail condensation reactions between allylic prenyl diphosphates. In this study, we characterize a cis‐prenyltransferase homolog from a methanogenic archaeon, Methanosarcina a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…In S. acidocaldarius , apparently only trans -geranylgeranyl pyrophosphate serves this role [92]. The recent report of one of the three cis -prenyltransferases in Methanosarcina acetivorans being able to catalyze both head-to-tail and non-head-to-tail condensation reactions [105] could reflect yet another unique aspect of archaeal phosphodolichol biosynthesis. In the hyperthermophile Aeropyrum pernix (optimal growth at 90–95°C [106]), the cis -prenyltransferase is unusual in that the substrate is the C 25 trans -geranylfarnesyl pyrophosphate [107].…”
Section: Phosphodolichol Biosynthesis In Archaeamentioning
confidence: 99%
See 1 more Smart Citation
“…In S. acidocaldarius , apparently only trans -geranylgeranyl pyrophosphate serves this role [92]. The recent report of one of the three cis -prenyltransferases in Methanosarcina acetivorans being able to catalyze both head-to-tail and non-head-to-tail condensation reactions [105] could reflect yet another unique aspect of archaeal phosphodolichol biosynthesis. In the hyperthermophile Aeropyrum pernix (optimal growth at 90–95°C [106]), the cis -prenyltransferase is unusual in that the substrate is the C 25 trans -geranylfarnesyl pyrophosphate [107].…”
Section: Phosphodolichol Biosynthesis In Archaeamentioning
confidence: 99%
“…In plants, where cis -prenyltransferases exist as enzyme families, it was shown that select family members that contribute to dolichol biogenesis also interact with a NogoB receptor homologue [103,110]. Although phylogenetic analysis has raised the possibility of such a protein in Archaea [105], evidence for the involvement of a NogoB receptor homologue in archaeal cis -prenyltransferase activity has yet to be presented.…”
Section: Phosphodolichol Biosynthesis In Archaeamentioning
confidence: 99%
“…Fifth, metabolic pathways for incorporating the methylated sulfur compound, methylmercaptopropionate, have been added/updated based on recent molecular biology studies [57]. Finally, several genes and a recently characterized reaction have been added to lipid biosythesis [5860]. …”
Section: Resultsmentioning
confidence: 99%
“…At first glance, this may appear to be in conflict with previous reports showing that eukaryotic hCIT orthologs heterologously expressed in S. cerevisiae were active without co-expression of NgBR/Nus1 orthologs. However, this can be explained due to the presence of the endogenous Nus1 in S. cerevisiae (7,10,(33)(34)(35)(37)(38)(39)(40). Furthermore, a number of hCIT orthologs in plants and protists that were studied in yeast are single-subunit enzymes that have been acquired through horizontal gene transfer, and are more closely related to EcUPPS than to hCIT (1,41).…”
Section: Discussionmentioning
confidence: 99%